A case of recalcitrant linear morphea responding to subcutaneous abatacept. Issue 2 (June 2021) - Talia, Jordan; Bitar, Carole; Wang, Yue; Whitfield, Michael L; Khanna, Dinesh
Introduction: Linear morphea is an inflammatory condition that is often treated with systemic glucocorticoids and methotrexate, with mycophenolate mofetil being used as an alternative agent. However, there are few published reports on beneficial effect of abatacept for refractory disease. We present a case of a woman in her 30s who presented with linear morphea on her scalp, with a notable response following the addition of subcutaneous abatacept. Methods: Computational analysis was performed comparing the immune cell scores of skin biopsies from five morphea skin biopsies from three additional unique patients and 15 healthy control skin biopsies. Value of p < 0.05 was considered statistically significant. Results: Immune cell scores demonstrated a statistically significant enrichment of activated CD4 memory T cells, M1 macrophages, monocytes, and memory B cells comparing skin biopsies of morphea versus healthy controls (p < 0.05 for all). Discussion: Abatacept may be considered for recalcitrant cases of morphea. Our computational analysis supports a well-designed study is needed to assess abatacept as first-line therapy.